Sejarah, Faktor-Faktor, Karakteristik Filsafat Umum - Candra Widan; Muhammad Fikri Aimar; M. Hafiz Arfatha; Heru Syahputra (Mathematics Education Study Program, 2025)
This paper explores the development of general philosophy, highlighting the contributions of various eras of thought from ancient Greek philosophy to modern and contemporary philosophy. This research uses a descriptive qualitative method with a historical-philosophical approach. Data collection was carried out through a literature review which included books, journal articles and documents related to the development of general philosophy from various eras. This study underlines the important role of figures such as Socrates, Plato, Aristotle, as well as modern thinkers such as Descartes and Kant in shaping philosophical discourse which includes metaphysics, epistemology, ethics and aesthetics. With a historical-philosophical approach, this research identifies the main characteristics of general philosophy, such as radical thinking, hunting for truth, and seeking clarity.